CONTEMPORARY SPIRITUALITIES IN THE 21TH CENTURY CATHOLIC SOCIAL DISCOURSE - Klauza, Karol (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article analyze the contemporary spirituality of art and its relation to culture. The reflections focus on the analysis of the social and religious phenomena characteristic of the early 21st century The documents of the Catholic Church, which refer to the spirituality in religious and social life, have been discussed. The reflections include the author’s systematics and the division of the types of spirituality of modern social life.